Pengaruh Motivasi Entertainment, Pass Time, dan Self Presentation Terhadap Hubungan Parasosial Penonton Netflix - Aaliyah Aulia; Jenny Ratna Suminar; Ditha Prasanti (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
The Netflix platform is no longer a stranger today, especially for film lovers during the Covid-19 pandemic. This phenomenon is interesting to study, in terms of knowing the influence of entertainment motivation, pass time and self-presentation on parasocial relationships in Netflix platform streaming users during the Covid-19 pandemic using the uses and gratfications theory as a framework and the initial basis for this research. The data used in this study were collected using a questionnaire with the help of Google Form to facilitate the distribution of questionnaires to Netflix users. Research sampling uses a non-probability sampling method, with a derivative of the convenience sampling method to increase data accuracy. The population in this study are Netflix users in Indonesia. The required sample size is calculated using the help of the G Power application. After obtaining 216 respondents, the data needed was then analysed using multiple linear regression tests on IBM SPSS. The results of this study show that entertainment motivation has a significant effect of 0.271 while self presentation motivation has a significant effect of 0.966 on the parasocial relationships of Netflix viewers during the Covid-19 pandemic. However, pass time motivation has no influence on the parasocial relationship of Netflix viewers during the Covid-19 pandemic.ABSTRAK Platform Netflix bukan menjadi hal yang asing lagi saat ini, terutama bagi para pecinta film pada masa pandemic Covid-19. Fenomena ini menarik untuk diteliti, dalam hal mengetahui pengaruh motivasi entertainment, pass time dan self presentation terhadap hubungan parasosial pada pengguna streaming platform Netflix selama pandemic Covid-19 menggunakan teori uses and gratfications sebagai kerangka berpikir dan landasan awal dibuatnya penelitian ini. Data yang digunakan dalam penelitian ini, dikumpulkan menggunakan kuesioner dengan bantuan Google Form untuk mempermudah penyebaran kuesioner kepada para pengguna Netflix. Pengambilan sampel penelitian menggunakan metode non-probability sampling, dengan turunan metode convenience sampling untuk menambah akurasi data. Populasi pada penelitian ini adalah para pengguna Netflix di Indonesia. Besaran sampel yang dibutuhkan dihitung menggunakan bantuan aplikasi G Power. Setelah mendapat 216 responden data yang dibutuhkan, selanjutnya dianalisis menggunakan uji regresi linear berganda pada IBM SPSS. Hasil dari penelitian ini menunjukkan jika motivasi entertainment memiliki pengaruh yang signifikan sebesar 0.271 sedangkan motivasi self presentation memiliki pengaruh yang signifikan sebesar 0.966 terhadap hubungan parasosial penonton Netflix selama pandemi Covid-19. Namun, motivasi pass time tidak memiliki pengaruh pada hubungan parasosial penonton Netflix selama pandemi Covid-19.